Integrasi Pendidikan Islam Berbasis Ilmu Sosial Profetik dalam Penguatan Keberagamaan Mahasiswa - Muhamad Ridwan Effendi; Rihlah Nur Aulia; Amaliyah Amaliyah; Naila Fathiya Salsabila (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
This research is based on integrating Islamic values through contemporary social theory to improve the degree of religious students in educational and learning activities in universities. This study aims to determine the paradigm foundation, essence, and relations of humanization, liberation, and transcendence of Kuntowijoyo's prophetic social sciences in Islamic education. The research was conducted using literature studies using a socio-historical philosophical approach. The data were obtained from several kinds of literature, adapted by direct and indirect quotation techniques, and then processed and analyzed with intelligent analysis methods in the three domains of Kuntowijoyo's prophetic social sciences, namely humanization ('Amar ma'rÅ«f), liberation (nahyÄ« munkar), and transcendence. The results showed that prophetic social science is a choice in the scientific discourse of Islamic socio-cultural formats that are interesting to be developed by Muslims in general, as well as the academic community of universities as part of academia. This is because Islamic education that develops is not only a process of instilling moral values and fortifying harmful access but also how these moral values are instilled able to act as Islamic forces to get out of poverty, ignorance, and social and cultural backwardness.